해방 후 북한의 소련군과 북한 주민의 루소포비아, 1945-1950 - 宋浚瑞; Joonseo Song (중소연구, 2023)
해방 직후 북한에 진주한 소련군이 북한 주민들로부터 루소포비아를 유발한 데에는 소련군의 약탈과 부녀자 강간 등 일탈행위뿐만 아니라 소련군의 조직적인 물자반출도 큰 영향을 미쳤다. 이 문제에 대해 선행연구가 잘 다루지 않거나 또는 파편적으로 다루고 있는 부분은 소련군의 일탈 및 일탈 감소의 원인, 그리고 소련군에 의한 물자반출의 구체적인 상황과 그에 대한 북한 주민의 적극적 대응으로서의 반대시위와 사보타주 행위에 관한 것이다. 본 연구는 이에 대해 북한 주민의 회고록, 자서전은 물론 러시아문서보관소자료를 교차검토하고 당시 북한 주둔 소련군의 상황을 소련 국내 경제 사정 및 전후 독일 주둔 소련군의 행태와 비교검토하면서 연구의 공백을 메우고자 하였다. This paper aims to explore the Russophobia among the residents of North Korea during the immediate post-colonial years. In addition to the deviant behavior of Soviet troops, which included looting and rape, the systematic removal of natural resources, grain, and machinery from North Korea by the Soviet troops significantly impacted the rise of Russophobia among North Koreans. Aspects not fully addressed in existing literature include the reasons for the deviant behavior of the Soviet troops, the subsequent decrease in such behavior, and a detailed analysis of the Soviet troops extracting various goods and resources from North Korea. The paper also delves into the proactive responses of the North Korean people, which included protests and acts of sabotage. This study examines these topics through a careful examination of memoirs and autobiographies of North Koreans, Russian archival materials, and by comparing the situation of Soviet troops in North Korea to the domestic economic situation in the contemporary Soviet Union and the behavior of Soviet troops in Germany during the post-World War II years.